An Alternative Splicing Program for Mouse Craniofacial Development - Hooper, Joan E.; Jones, Kenneth L.; Smith, Francis J.; Williams, Trevor; Li, Hong (Frontiers in Physiology, 2020)
Alternative splicing acts as a fundamental mechanism to increase the number of functional transcripts that can be derived from the genome - and its appropriate regulation is required to direct normal development, differentiation, and physiology, in many species. Recent studies have highlighted that mutation of splicing factors, resulting in the disruption of alternative splicing, can have profound consequences for mammalian craniofacial development. However, there has been no systematic analysis of the dynamics of differential splicing during the critical period of face formation with respect to age, tissue layer, or prominence. Here we used deep RNA sequencing to profile transcripts expressed in the developing mouse face for both ectodermal and mesenchymal tissues from the three facial prominences at critical ages for facial development, embryonic days 10.5, 11.5, and 12.5. We also derived separate expression data from the nasal pit relating to the differentiation of the olfactory epithelium for a total of 60 independent datasets. Analysis of these datasets reveals the differential expression of multiple genes, but we find a similar number of genes are regulated only via differential splicing, indicating that alternative splicing is a major source of transcript diversity during facial development. Notably, splicing changes between tissue layers and over time are more prevalent than between prominences, with exon skipping the most common event. We next examined how the variation in splicing correlated with the expression of RNA binding proteins across the various datasets. Further, we assessed how binding sites for splicing regulatory molecules mapped with respect to intron exon boundaries. Overall these studies help define an alternative splicing regulatory program that has important consequences for facial development.